ANALISIS COST-VOLUME-PROFIT SEBAGAI ALAT BANTU PERENCANAAN LABA (MULTI PRODUK) PADA PERUSAHAAN PIA LATIEF KEDIRI - Winarko, Sigit Puji; Astuti, Puji (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2018)
Every company wants sustainability in its business. To be able to continue to live and grow the company needs profit, because with profits obtained then the company’s capital will increase. Increased capital causes the company to grow and can meet all of its operational needs. To earn a profit, it takes careful planning in its business, starting from sales, cost, and targeted profit. Therefore, the analysis of cost volume and profit becames one away to achieve the desired profit of company, so that the companyy can grow. In this research, the objective to be achieved is to determine the break evenpoint, margin contribute, and margin of safety of Pia Latief product in multi product. The analysis used is a quantitative approach that uses secondary data. In the separation of varaibel costs and fixed costs on overheads used the method of the highest point and the lowest point. Company Pia Latief produces two types of pia, namely wet pia and dry pia. Results of research conducted in 2017 obtained break evenpoint wet pia 10,707 units and dry pia of 6,227 units. Contribution margin in 2017 amounted to Rp 1,873,010,837, - while the ratio was 55.2%. Margin of safety from wet pia is 96.21% while dry pia is 96.2%. To achieve a 5% increase in profit by 2018, the company must sell 297,072 units of wet pia and 172,184 dry pia units. Keywords: cost volume profit, profit planning, multi product